2008
DOI: 10.1111/j.1553-2712.2008.00233.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching and Assessing Procedural Skills Using Simulation: Metrics and Methodology

Abstract: Simulation allows educators to develop learner-focused training and outcomes-based assessments. However, the effectiveness and validity of simulation-based training in emergency medicine (EM) requires further investigation. Teaching and testing technical skills require methods and assessment instruments that are somewhat different than those used for cognitive or team skills. Drawing from work published by other medical disciplines as well as educational, behavioral, and human factors research, the authors dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 50 publications
0
66
0
3
Order By: Relevance
“…Real-time video and audio projection allows for feedback, education, and observation. 13 These models can be prohibitively expensive to purchase, require maintenance, and are fragile.…”
Section: High-fidelity Manikinsmentioning
confidence: 99%
“…Real-time video and audio projection allows for feedback, education, and observation. 13 These models can be prohibitively expensive to purchase, require maintenance, and are fragile.…”
Section: High-fidelity Manikinsmentioning
confidence: 99%
“…13,14 Others have demonstrated that simulated experiences are useful adjuncts to fill training gaps. [6][7][8][15][16][17] More evidence is available to suggest that simulated experiences increase procedural knowledge, skill, and behaviours and may improve patient outcomes. The educational intervention, which included both screen-based learning and hands-on learning with feedback, was carefully designed to include several important instructional design features for simulation.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8][9][10] Although various different chest tube insertion task trainers exist, there is no objective and validated scoring system in the literature to assess chest tube insertion competency. Such a tool could be used to assess a practitioner's skill, identify areas for improvement, or rate on a scale for high-stakes assessment (either in the simulated or real environment).…”
mentioning
confidence: 99%
“…Los alumnos a los que se les ofrece esta oportunidad de implicarse en la práctica deliberada y repetitiva con simulación parecen adquirir las habilidades necesarias en periodos más breves que aquellos que se exponen únicamente a las situaciones clínicas rutinarias con pacientes reales. De hecho, existe relación entre el tiempo total de exposición a actividades de simulación y los resultados de aprendizaje [11,12]. Que los estudiantes participen en escenarios simulados de alto realismo como los descritos en este trabajo, en unas cuatro o cinco ocasiones a lo largo del curso, parece un compromiso razonable entre lo ideal y lo factible.…”
unclassified